2023
DOI: 10.3390/cimb45010029
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Gene Regulatory Network of Transcription Factors Related to the Hallmarks of Cancer

Abstract: The transcriptomic analysis of microarray and RNA-Seq datasets followed our own bioinformatic pipeline to identify a transcriptional regulatory network of lung cancer. Twenty-six transcription factors are dysregulated and co-expressed in most of the lung cancer and pulmonary arterial hypertension datasets, which makes them the most frequently dysregulated transcription factors. Co-expression, gene regulatory, coregulatory, and transcriptional regulatory networks, along with fibration symmetries, were construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 174 publications
0
11
0
Order By: Relevance
“…Using differentially expressed genes (DEGs) and phosphosites (DEPPs) expression, we predicted TF activity ( Supplementary Table 5B ) and kinase activity ( Supplementary Table 5C ) by “DoRothEA” and “PHONEMeS” packages in R. A total of 26 TFs associated with lung cancer, encompassing both NSCLC and SCLC 27 , have been identified as frequently dysregulated in lung tumoral cells. Utilizing these TFs, we conducted a comparative analysis between two sample sets, each representing different storage periods ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…Using differentially expressed genes (DEGs) and phosphosites (DEPPs) expression, we predicted TF activity ( Supplementary Table 5B ) and kinase activity ( Supplementary Table 5C ) by “DoRothEA” and “PHONEMeS” packages in R. A total of 26 TFs associated with lung cancer, encompassing both NSCLC and SCLC 27 , have been identified as frequently dysregulated in lung tumoral cells. Utilizing these TFs, we conducted a comparative analysis between two sample sets, each representing different storage periods ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…We further input gene lists of corresponding gene clusters of bone marrow B cell learned by gene cluster within Metascape [2], protein-protein interaction enrichment analysis has been carried out with the following databases: STRING [3], BioGrid [4], OmniPath [5], and InWeb IM [6]. Only physical interactions in STRING (physical score larger than 0.132) and BioGrid are used (details).…”
Section: (Supplementary)mentioning
confidence: 99%
“…Gene Regulatory Networks (GRNs) within single-cell RNA sequencing (scRNA-seq) datasets present a sophisticated interplay of transcription factors (TFs) and target genes, uniquely capturing the modulation of gene expression and thereby delineating the intricate cellular functions and responses within diverse cell populations [1]. GRNs illuminate core biological processes and underpin applications from disease modeling to therapeutic design [2, 3, 4], empowering researchers to interpret the mechanisms of gene interactions within cells and leverage this understanding for medical and biotechnological innovations [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Like many other genes involved in the regulation of development, SOX genes are frequently dysregulated in cancer. A large amount of RNA-seq data revealed that SOX genes are aberrantly expressed in a variety of solid tumors, including bladder carcinoma [ 18 ], prostate carcinoma [ 19 ], renal cell carcinoma [ 20 ], liver carcinoma [ 21 , 22 ], sarcoma [ 22 ], cervical carcinoma [ 23 ], breast carcinoma [ 24 ], and lung carcinoma [ 25 ].…”
Section: The Role Of Sox Genes In Glioblastomamentioning
confidence: 99%